2010
DOI: 10.1016/j.trstmh.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of poliovirus neutralizing antibodies in São Paulo State, Brazil

Abstract: As the world envisions poliomyelitis eradication, objective parameters are needed to ascertain whether immunocompetence against the virus provided by vaccine campaigns has been attained. The presence of neutralizing antibodies is considered a surrogate marker of protective immune response to the agent. Neutralization of three poliovirus serotypes were evaluated in a total of 411 sera samples collected from 1999 to 2005 in São Paulo State, Brazil. Antibody titres >/=1:8 were presented at 88.1% (362/411), 88.8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
2
2
0
2
Order By: Relevance
“…Therefore, true eradication can only be achieved if population immunity gap is closed, all circulating vaccine‐derived polioviruses are eliminated and immunity to all poliovirus types in all populations is balanced. Consistent with reports from Brazil, no significant difference was observed in P1, P2, and P3 immunity in children aged 0–5 years [Luchs et al, 2010] but worthy of note is the fact that Brazil is presently a Polio‐free country while Nigeria is still endemic with wild poliovirus. Similarly, no correlation between gender and antibody to poliovirus types was observed in agreement with a previous report [Adewumi et al, 2006].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, true eradication can only be achieved if population immunity gap is closed, all circulating vaccine‐derived polioviruses are eliminated and immunity to all poliovirus types in all populations is balanced. Consistent with reports from Brazil, no significant difference was observed in P1, P2, and P3 immunity in children aged 0–5 years [Luchs et al, 2010] but worthy of note is the fact that Brazil is presently a Polio‐free country while Nigeria is still endemic with wild poliovirus. Similarly, no correlation between gender and antibody to poliovirus types was observed in agreement with a previous report [Adewumi et al, 2006].…”
Section: Discussionsupporting
confidence: 85%
“…The decrease of seroprevalence for P3 was also showed similarly in other serological studies [26][36], particularly in teenagers and young adults [29], [34]. It may be explained by a lower potency of P3 antigens in trivalent OPV, with suboptimal levels of protection for P3 following OPV immunization [37].…”
Section: Discussionsupporting
confidence: 80%
“…Lower seroconversion rates have been observed for P3 following OPV immunization (33). Luchs and colleagues in Brazil demonstrated that seropositivity to P1 and P2 increased with increasing age and peaked in children 6 to 15 years old, while seropositivity to P3 declined with increasing age from 71.1% in children 0 to 5 years old to 51.8% in children older than 15 years (21). This is likely a result of low vaccine immunogenicity of P3 and/or low initial P3 antibody titers that eventually fell below the detection limits as time passed (34).…”
Section: Discussionmentioning
confidence: 99%